Evaluation of molecular and genetic approaches to generate glucoamylase overproducing strains of Aspergillus niger. - Verdoes, J.C.; Van Diepeningen, A. D.; Punt, P. J.; Debets, A. J.; Stouthamer, A. H.; Van Den Hondel, C. A.
To evaluate the possibility of improving glucoamylase (GLA)production in Aspergillus niger strains carrying multiple copies of the GLA encoding gene (glaA), additional glaA copies were introduced either by genetic recombination or retransformation. For strains to be used in such experiments a genetic analysis was first carried out. The results of this analysis clearly revealed that in each transformant intergration had occurred at a chromosome corresponding to a single linkage group (LG). The GLA production per gene copy showed considerable variation in these strains, indicating a clear effect of the site of integration on gene expression. Introduction of additional gene copies by genetic recombination experiments was carried out for different combinations of strains, carrying glaA copies in different chromosomes. The introduction of additional glaA gene copies by genetic recombination did not result in a considerable increase in GLA production compared to the parental strains. In some strains recombination resulted in genetic instability, observed by the frequent loss of glaA copies. Also, retransformation of multi-copy glaA strains did not result in an increase in GLA production. In several strains even a decrease in GLA production was found after retransformation. Southern analysis of these transformants suggested that newly introduced gene copies were heavily rearranged, which partly explains why GLA production was not increased. Further analysis of one such transformant provided evidence that the overexpression of the glaA gene is limited by the amount of trans-acting regulatory protein(s)available
Keywords: GENETIC STABILITY; PROTEIN OVERPRODUCTION; CHEF ANALYSIS; GENE REGULATION; FILAMENTOUS FUNGI